Pengaruh Edukasi Kesehatan Berbasis Budaya Nggempe terhadap Pengetahuan Calon Pengantin tentang Persiapan Kehamilan Sehat Melalui Layanan Homecare - Wahyuningsi, Sri; Saudia, Baiq Eka Putri; Hanafi, Fachrudi (Poltekkes Kemenkes Mataram, 2025)
Maternal Mortality Rate,Infant Mortality Rate and stunting are still the main problems in improving health indicators, especially in Indonesia. In Kota Bima, the incidence of pregnant women with complications still exceeds the target rate of 20%, namely 36.41%. These problems can start from the pre-conception period. Bride and groom are a strategic target group in efforts to improve pre-conception health. This of course can pose various kinds of risks such as disease transmission, high-risk pregnancies and even maternal and infant mortality. By taking advantage of the cultural momentum leading up to the wedding, namely the